Hadith of associated with the target of communication (communicating with oneself and communicating with others) - Muya Syaroh Iwanda Lubis; Sabrina Aulia Rahmah; Asrindah Nasution; Maria Ulfa Batoebara; Ahmad Taufiq Harahap (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2022)
ABSTRACTBasically the nature of communication is any form of interaction among human beings. The two communication takes place in almost every aspect of human life. Every human living person is inherently free from waking up to sleeping, engaging in communication. It has been suggested in one study that 60% to 80% of people build up to communicate, as a result of communication as a determinant of the insan's biological qualities. Three so wide is communication to human relationships as a sign of how important communication is to life. Even communicating includes the most obvious needs as important as eating & drinking.Communication occurs as a consequence of social interaction. Society is at least 2 people who work with each other who, because they work together, cause social relations. We're basically in communication mode since we were born global. This act of communication was monotonous during his life process. Communication thus became the lifeblood of human life.6 Nir can be imagined what this global insan's & features of life would look like if there were only sporadic or almost automatic action of communication between one person/one group of people using the other mob.Keyword: hadith, target of communication.